Assessment of influences of cooking on cadmium and arsenic bioaccessibility in rice, using an in vitro physiologically-based extraction test. (15th December 2016) - Zhuang, Ping; Zhang, Chaosheng; Li, Yingwen; Zou, Bi; Mo, Hui; Wu, Kejun; Wu, Jingtao; Li, Zhian
Highlights: Cooking reduced bioaccessibility of Cd and As in rice. Cadmium bioaccessibility was higher in gastric than gastrointestinal phase. Arsenic bioaccessibility was higher in gastrointestinal than gastric phase. Different water to rice ratio has different changes on metal(loid)s bioaccessibility. Abstract: The health risks associated with rice consumption may decrease if consumers use cooking practices which can reduce the bioaccessibility of metal(loid)s. The effects of cooking on the Cd and As bioaccessibility, at three contamination levels of rice, were studied. Results indicated that cooking reduced bioaccessibility of Cd and As in rice. Cooking resulted in a significant increase (p < 0.01) of Cd and As concentrations in the residual fraction. Low volume water-cooking of rice to dryness reduced total Cd by about 10% for rices A and B, while medium or high volume water-cooking had no effect on Cd bioaccessibility in all rice types. In contrast, low volume cooking did not remove As, but a significant decrease (p < 0.05) was observed when cooking with higher volumes of water. This study provides information for a better understanding of more realistic estimation of metal(loid)s exposure from rice and the possible health risks.